Experiment System of Motorcycle Impact Injury Using Electric Motor Traction - Haibin CHEN; Jianjin HANG; Liying ZHANG; Xin NING; Xiaoyan LI; Zhiyong YIN; Guangyu YANG; Zhengguo WANG (Institute of Advanced Engineering and Science, 2013)
A unique motor drive unit (MDU) and motorcycle crash simulation unit (MCSU) were developed to establish a short-track and high-accuracy experiment system of motorcycle impact injury. The control hardware of the MDU consists of a “two DC motors” system and a “two drums, closed-loop, friction transmission” system, and the control software of the MDU has a novel “carriage acceleration profile control program” which was specially set up to prevent the cusp-like pulse and oscillation phenomenon in the acceleration stage close to the uniform velocity. The unique motorcycle sled and energy absorber constitute a novel MCSU. Research results show that: (1)Using a unique generation algorithm of the carriage acceleration- and velocity-time curve and unique manufacturing techniques of hardware components, the apparatus presented in this paper has a potential to become the first short-track experiment system of motorcycle impact injury. (2)Due to a high weight capacity with the ability to propel whole vehicles, the MDU can be used in the full motorcycle/full vehicle crash tests or vehicle component sled impact tests. DOI: http://dx.doi.org/10.11591/telkomnika.v11i4.2429